The recent colonization of south Brazil by the Azores chromis Chromis limbata - A. B. Anderson; E. M. Salas; L.A. Rocha; S. R. Floeter (Journal of Fish Biology, 2017)
The damselfish Chromis limbata is native to the Macaronesian Archipelagos (Azores, Madeira and Canaries) and the western coast of Africa between Senegal and Angola. During the austral summers of 2008 and 2009 the species was recorded for the first time in the south‐western Atlantic Ocean around Campeche and Xavier Islands, in Florianópolis, Santa Catarina State, Brazil. Here, the progression of C. limbata in southern Brazilian waters is described using visual counts and genetic surveys and changes in the density of the native congener Chromis multilineata were also investigated. Underwater visual censuses of both Chromis species were carried out from 2009 to 2014. Chromis limbata tissue samples were collected and the mtDNA control region was sequenced and compared with mtDNA haplotypes from the natural range to confirm species identity, compare genetic diversity and to infer connectivity between newly established Brazilian populations. The Brazilian population of C. limbata increased significantly over the past 5 years and the effect on C. multilineata is still an open question, longer time‐series data will be necessary to clarify possible interactions. The molecular analyses confirmed species identity, revealed strong haplotype connectivity among Brazilian study sites and showed a low genetic diversity in Brazil when compared with the native populations, suggesting few individuals started the invasion. Four hypotheses could explain this colonizing event: C. limbata was released by aquarium fish keepers; larvae or juveniles were transported via ship ballast water; the species has rafted alongside oil rigs; they crossed the Atlantic Ocean through normal larval dispersal or naturally rafting alongside drifting objects. The rafting hypotheses are favoured, but all four possibilities are plausible and could have happened in combination.